Social media in the development of sustainable business - Cristian Bogdan Onete; Razvan Dina; Denisa Elena Vlad (Amfiteatru Economic Journal, 2013)
Due to the transformations appeared in the contemporary society, the way natural resources are used, at the United Nations it has been ascertained that a development strategy must be found, strategy which would lead to an effective use or preservation of these ones for the following generations. The use of certain tools to streamline the activities and at the same time to reduce the use of exhaustible resources is required. The businesses conducted in the virtual environment can be an effective way to reach this purpose and social media provides the necessary tools to develop this kind of business. Within this article are presented the ways that social media can become a platform for sustainable business and a support for the development of goods and services that can become sustainable. To determine the image that business environment has on these aspects, a research has been carried out to determine the perception regarding social media and how sale and marketing activities can be realized through the agency of this one.
Keywords: Q01; M19; M20; M31; 330; Social media; sustainable business; marketing; new consumer; innovation